"Hot Tub Lung" With M. avium complex in an Immunocompetent Adolescent. Issue 3 (5th December 2022) - Waletzko, Benjamin; Lin, Philana Ling; Lopez, Santiago M.C.
Abstract : We describe a case of pulmonary Mycobacterium avium complex (MAC) infection in an immunocompetent pediatric patient after a hot tub near drowning event with a literature review of pediatric MAC-associated disease after hot tub exposure.